Religious Awareness and Ritual Practices in The Tarekat Qadiriyah wa Naqsyabandiyah Suryalaya - Jamaludin Jamaludin; Solihah Sari Rahayu; Muhamad Dani Somantri (Islamica: Jurnal Studi Keislaman, 2021)
This article seeks to reveal the religious experiences of the members of the Tarekat Qadiriyah wa Naqsyabandiyah (TQN) in Suryalaya, Tasikmalaya, West Java. Using a phenomenological approach, this article finds that TQN followers exhibit religious awareness and obedience to legal norms, reflected in various ritual practices, such as dhikr (remembrance), khataman (completing the reading of the Qur’ān), manakiban (reciting the saint’s hagiography), riyāḍah (spiritual exercises), tawassul (mediating), and ḥajj (pilgrimage). The religious awareness is built upon the belief in achieving good morality as the attribute of a perfect man (insān kāmil). The socio-structural diversity of the TQN community in social life is manifested in the complexity of hierarchies involved in the tarekat system: murshid (spiritual leader); representatives of talqīn which include intellectuals/modernist, ulama/ traditionalist, scholar/neo-traditionalist; preachers from the realms of pesantren, university, and politics. This article argues that the relationship between different hierarchies of membership in the TQN with regard to religious awareness is based on the understanding of the tarekat teaching provided by the spiritual leader.